(untitled) (Nigerian Journal of Technology, 2020)
This work evaluate the influence of waste pure water sachet (WPS) as a modifier in Hot Mix Asphalt (HMA). The properties of the constituent materials were determined. Modified HMA samples were prepared at varying concentration of 2, 4, 6, 8 and 10% WPS content by weight of the Optimum Binder Content (OBC). The properties of the modified HMA were determined using Marshall Method of mix design. The properties of the constituent materials showed that they are suitable for HMA production. The modified bitumen showed an increase in softening point (61 – 73.5%), flash point (258 – 2820C), fire point (289 – 3110C) and ductility (92.67 – 118.67cm) as the WPS content increases from 2% to 10% while decrease in penetration (62.33 – 56.5mm) as WPS content increases from 2% to 6%. Stability and Bulk density increases from 4.64kN to 8.84kN and 2.21g/cm3 to 2.34g/cm3 respectively while flow, voids in mineral aggregates (VMA) and Air voids decreases from 3.6 to 2.98mm, 23.85 to 20.16% and 19.73 to 13.97% respectively as the WPS content was increased from 2 to 8%. An optimum polyethylene from WPS modifier content of 8% by weight of the OBC is recommended for use in the HMA. http://dx.doi.org/10.4314/njt.v39i4.10